First report of Phoma sorghina (Sacc.) Boerema Dorenbosch & van Kest on wheat leaves (Triticum aestivum L.) in Argentina - Perelló, Analía Edith (2005)
A new disease caused by Phoma sorghina has been detected for the first time on wheat plants in the Province of Buenos Aires, Argentina. The pathogen was isolated from wheat leaves growing under field conditions, cultured on PDA and identified by its morphobiometric and cultural characters. The disease symptoms and morphological characters of the pathogen are described. Pathogenicity of the isolate was confirmed by inoculating 10 wheat cultivars under greenhouse conditions.